On Some Properties of Focal Points - M. R. Ferchichi; I. Djellit (Discrete Dynamics in Nature and Society)
We consider some dynamical properties of two-dimensional maps having an inverse with vanishing denominator. We put in evidence a link between a fixed point of a map with fractional inverse and a focal point of this inverse.